PERAN GURU DALAM MEMBENTUK LINGKUNGAN BELAJAR MULTIKULTURAL YANG INKLUSIF - SYAMSUARDI, EZI MULIA; Ridha, Abdurrasyid; Yolanda, Dilla; Hudia, Tasya (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This article reviews the role of teachers in shaping an inclusive multicultural learning environment in Indonesia, recognizing the importance of multicultural education as a response to the country's rich cultural, ethnic and religious diversity. Teachers are not only the deliverers of subject matter, but also the facilitators of learning who have a major impact in shaping the characteristic foundations of their learners. In detailing this approach, teachers are not only educators but also architects of environments that create inclusive spaces. The role of teachers in shaping students' attitudes and understanding of cultural diversity is crucial in the face of social change and globalization. Multicultural education views teachers as agents of change who are responsible for shaping students' attitudes, values and understanding of cultural diversity. Teachers also have a key role in creating safe and supportive learning spaces, ensuring the implementation of rules and norms oriented towards equality, justice and respect for diversity. Integrating multicultural values in the curriculum is an important foundation for teachers, involving the selection of learning materials that reflect cultural diversity. Teachers are also involved in multicultural skills training, opening the door to a more inclusive and responsive education to student diversity. As such, this article provides an in-depth look at the role of teachers as agents of change in creating a multicultural and inclusive educational environment in Indonesia, shaping a generation that is open, tolerant and appreciative of diversity in society.As such, this article provides an in-depth look at the role of the teacher as a teacher.